O ensino religioso nas escolas públicas = THE RELIGIOUS TEACHING IN PUBLIC SCHOOLS - Bertoni, José Carlos (2009)
Marcado por conflitos na escola pública brasileira desde sua origem e por uma forte presença da religião cristã, o Ensino Religioso no Brasil evoluiu no seu processo histórico. De uma concepção catequética e unirreligiosa nos primórdios da colonização, o Ensino Religioso passou para uma con-cepção plurirreligiosa a partir da laicização do Estado como tentativa de superar o proselitismo e promover um diálogo, especialmente, entre as re-ligiões cristãs. Já nos últimos anos, esse ensino evoluiu para uma proposta transreligiosa com o propósito de reler o fenômeno religioso como área de conhecimento e como parte da formação básica do cidadão, assegurando o respeito à diversidade religiosa brasileira. Este artigo apresenta um pano-rama da evolução do Ensino Religioso nas Leis de Diretrizes e Bases e uma análise da concepção proposta pela última LDB
Distinguished by conflicts in Brazilian public schools since its origin and by a strong presence of Christian religion, the Religious Teaching in Brazil developed within its historic process. From a catechetical and uni-religious concept in the beginning of Brazil’s colonization, the Religious Teaching evolved to a pluri-religious concept with the State becoming more lay as an attempt to overcome proselytism and to foster a dialogue especially between Christian religions. Recently it has moved to a trans-religious ap-proach aiming to reinterpret the religious phenomenon as a field of kno-wledge and as part of the citizen’s basic formation, assuring respect for the Brazilian religious diversity. This article offers a survey of the Religious Teaching evolution according to the Lei de Diretrizes e Bases (Guidelines and Bases Law) and an analysis of the concept suggested by the last LDB.
Keywords: Educação; Education; Ensino Religioso; Fenômeno religioso; Laicidade; Laity; Legislação de ensino; Religious Teaching; Religious Phenomenon; Teaching legislation